MENINGKATKAN KETERAMPILAN BERHITUNG PENJUMLAHAN BILANGAN CACAH SISWA KELAS 3 SEKOLAH DASAR MELALUI MEDIA PAPAN PINTAR BERHITUNG - Nurjanah, Nisful Laili; Hendratno; Jumiati; Yogga Agus Wahyudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study is to improve the addition skills of 3rd-grade students through the use of smart counting board media. The identified problem is the low learning outcomes of students in mathematics, particularly in the addition of whole numbers. This study employs classroom action research (CAR), which consists of two cycles. Planning, implementation, observation, and reflection are components of each cycle. The smart counting board media is used as a visual aid to promote active and interactive learning throughout each cycle. The results indicate a significant improvement in students' addition skills. In Cycle I, the percentage of students achieving the Minimum Completeness Criteria (MCC) was 60%, while in Cycle II it increased to 85%. Furthermore, students demonstrated a higher level of enthusiasm during the learning process, as evidenced by their increased participation in classroom activities. Thus, the use of smart counting board media has proven effective in enhancing the addition skills of 3rd-grade students. This study suggests that teachers should consider using interactive media when teaching mathematics to make the lessons more enjoyable and effective.